William Dole Fund Collection : Santa Barbara Museum of Art Contemporary Graphics Center. - Dole, William; Klausner, Betty (Santa Barbara : Santa Barbara Museum of Art, 1980)
Dole, William ; Thiebaud, Wayne ; Tullis, Garner ; Celmins, Vija ; Van Hoesen, Beth ; Summers, Carol ; Torlakson, James ; Cortright, Steven ; Oliveira, Nathan ; Wiley, William T. ; Sturman, Eugene ; Nauman, Bruce ; Hill, Charles Christopher ; Hockney, David ; Diebenkorn, Richard ; LeWitt, Sol ; Acconci, Vito ; Raffael, Joseph ; Marioni, Tom ; Fox, Terry ; Burden, Chris ; Steir, Pat ; Johnson, Don ; McCoy, Ann ; Treiman, Joyce ; Ruscha, Ed ; Vaccarino, Robin ; Davis, Ron ; Goode, Joe ; Arneson, Robert ; Allen, Terry
Santa Barbara Museum of Art Contemporary Graphics Center - William Dole Fund Collection, Santa Barbara Museum of Art, Santa Barbara, from October 11 through November 23, 1980
Engels
boek